Preparation and characterization of mixed matrix membranes based on poly(vinylidene fluoride) and zeolite 4A for gas separation - Shen, Yi. (2013)
Zeolite 4A was incorporated into poly(vinylidene fluoride) (PVDF) matrix to prepare mixed matrix membranes (MMMs). The objective of this study was to investigate the effects of the inorganic filler on the structural properties of the MMMs. The resulting membranes were characterized using thermogravimetric analysis, differential scanning calorimetry, X-ray diffraction, contact angle tests, and scanning electron microscopy (SEM). The mechanical properties of the membranes were determined using a tensile stress–strain machine. To fully study the interface properties between the inorganic fillers and polymer chains, the densities of the membranes were experimentally determined and compared with the theoretical values. The experimental densities of the composite membranes were lower than those of the theoretical values. The void volume fractions were calculated accordingly. The single gas (He, CO2, O2, and N2) permeabilities of the resulting membranes were carried out. The highest permeabilities of 14.65, 6.62, 1.01, and 0.3 Barrer for He, CO2, O2, and N2, respectively, were obtained by PVDF/4A 32% composite membrane; whereas the highest selectivities of 105.5, 31.5, and 3.3 for He/N2, CO2/N2, and O2/N2, respectively, were obtained using PVDF/4A 16% composite membrane.